Distinct roles of FKF1, GIGANTEA, and ZEITLUPE proteins in the regulation of CONSTANS stability in Arabidopsis photoperiodic flowering - Song, Young Hun (Proc Natl Acad Sci U S A, 2014)
Many plants measure changes in day length to synchronize their flowering time with appropriate seasons for maximum reproductive success. In Arabidopsis, the day-length–dependent regulation of CONSTANS (CO) protein stability is crucial to induce FLOWERING LOCUS T (FT) expression for flowering in long days. The FLAVIN-BINDING, KELCH REPEAT, F-BOX1 (FKF1) protein binds to CO protein specifically in the long-day afternoon and stabilizes it, although the mechanism remains unknown. Here we demonstrated that the FKF1-interacting proteins GIGANTEA (GI) and ZEITLUPE (ZTL) are involved in CO stability regulation. First, our immunoprecipitation-mass spectrometry analysis of FKF1 revealed that FKF1 forms an S-phase kinase-associated protein 1 (Skp1)/Cullin(CUL)/F-box complex through interactions with Arabidopsis Skp1-like 1 (ASK1), ASK2, and CUL1 proteins and mainly interacts with GI protein in vivo. GI interacts with CO directly and indirectly through FKF1. Unexpectedly, the gi mutation increases the CO protein levels in the morning in long days. This gi-dependent destabilization of CO protein was cancelled by the fkf1 mutation. These results suggest that there are other factors likely influenced by both gi and fkf1 mutations that also control CO stability. We found that ZTL, which interacts with GI and FKF1, may be one such factor. ZTL also interacts with CO in vivo. The CO protein profile in the ztl mutant resembles that in the gi mutant, indicating that ZTL activity also may be changed in the gi mutant. Our findings suggest the presence of balanced regulation among FKF1, GI, and ZTL on CO stability regulation for the precise control of flowering time.